2011
DOI: 10.1063/1.3591155
|View full text |Cite
|
Sign up to set email alerts
|

Controlling polarization anisotropy of site-controlled InAs/InP (100) quantum dots

Abstract: We report on the shape and polarization control of site-controlled multiple and single InAs quantum dots (QDs) on InP pyramids grown by selective-area metal-organic vapor phase epitaxy. With increasing growth temperature the QDs elongate causing strong linear polarization of the photoluminescence. With reduced pyramid base/pyramid top area/QD number, the degree of polarization decreases, attributed to the symmetric pyramid top, reaching zero for single QDs grown at lower temperature. This control of linear pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
(24 reference statements)
1
12
0
Order By: Relevance
“…However, in addition to wavelength control, lateral ordering and position control are key challenges for future applications [3]. Selective-area growth of truncated InP pyramids has been widely used for the site-controlled InAs QD growth by metal organic vapor phase epitaxy (MOVPE) [4][5][6] and chemical beam epitaxy (CBE) [7]. If not close to pyramid pinch-off, however, the QDs are arranged randomly.…”
Section: Introductionmentioning
confidence: 99%
“…However, in addition to wavelength control, lateral ordering and position control are key challenges for future applications [3]. Selective-area growth of truncated InP pyramids has been widely used for the site-controlled InAs QD growth by metal organic vapor phase epitaxy (MOVPE) [4][5][6] and chemical beam epitaxy (CBE) [7]. If not close to pyramid pinch-off, however, the QDs are arranged randomly.…”
Section: Introductionmentioning
confidence: 99%
“…25 Interestingly, Yuan et al studied the shape and polarization control of site-controlled InAs QDs on InP pyramids. 39 They experimentally observed that with increasing the growth temperature of the QDs, linear polarization of the photoluminescence becomes stronger. 39 They also observed the degree of polarization decreases with decreasing the pyramid base/pyramid top area/QD number.…”
mentioning
confidence: 98%
“…39 They experimentally observed that with increasing the growth temperature of the QDs, linear polarization of the photoluminescence becomes stronger. 39 They also observed the degree of polarization decreases with decreasing the pyramid base/pyramid top area/QD number. 39 Such investigations 39 are of great importance for entangled photon sources.…”
mentioning
confidence: 98%
“…Therefore, a much easier and more robust method is to pattern a dielectric medium of certain geometry, containing the single emitter inside. Up to now, the existing reports concern almost exclusively the attempts on the polarization control in the spectral range below 1 µm, with only a single report on modifying the QD emission polarization at the 3 rd telecommunication window by tailoring a ridge waveguide structure [17].…”
Section: Introductionmentioning
confidence: 99%